2020
DOI: 10.1158/1078-0432.ccr-19-1702
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Extracellular Tumor pH to Reveal Effects of Locoregional Therapy on Liver Cancer Microenvironment

Abstract: Purpose: To establish magnetic resonance (MR)-based molecular imaging paradigms for the noninvasive monitoring of extracellular pH (pH e ) as a functional surrogate biomarker for metabolic changes induced by locoregional therapy of liver cancer.Experimental Design: Thirty-two VX2 tumor-bearing New Zealand white rabbits underwent longitudinal imaging on clinical 3T-MRI and CT scanners before and up to 2 weeks after complete conventional transarterial chemoembolization (cTACE) using ethiodized oil (lipiodol) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
(59 reference statements)
0
39
0
1
Order By: Relevance
“…Lamp2 has been described to be overexpressed in aggressive tumors and to be upregulated in acidosis-adapted tumor cells [ 34 ]. This protein has been proposed as a histologic marker for pathologic correlation with in vivo pH e mapping [ 46 ]. However, in our study Lamp2 was found to be upregulated only in Walker-256 cells and in AT1 tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Lamp2 has been described to be overexpressed in aggressive tumors and to be upregulated in acidosis-adapted tumor cells [ 34 ]. This protein has been proposed as a histologic marker for pathologic correlation with in vivo pH e mapping [ 46 ]. However, in our study Lamp2 was found to be upregulated only in Walker-256 cells and in AT1 tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Three well studied and characterized human hepatic cancer cell lines with varying growth characteristics were used: HepG2 (ATCC, Gaithersburg, MD; catalog no HB‐8065, ), Huh7 (CLS Cell Lines Services, Eppelheim, Germany; catalog no 300156/p7178_HuH7, ), and SNU475 (ATCC; catalog no CRL‐2236, ). Additionally, we used a human hepatocyte cell line derived from primary normal liver cells infected with SV40 large T‐antigen, THLE2 (ATCC; catalog no CRL‐10149, ), and a metastatic liver cancer cell line, VX2 (ATCC; catalog no CRL‐6503, ), which was derived from a sarcoma of a female New Zealand White rabbit, commonly used in a translational rabbit liver cancer model 21,24 . All experiments were performed in mycoplasma‐free cells and human cell lines have been authenticated using short tandem repeat genotype profiling within three years prior to experimental use.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, imaging of tumor metabolism in the TME serves as a predictive biomarker for individual susceptibility to oncological treatments. Additionally, it may enable earlier and more sensitive monitoring of tumor response to therapy that precedes morphological changes measurable with conventional anatomical imaging 11 …”
Section: Introductionmentioning
confidence: 99%
“…54 Recently scientists have proposed using high-resolution pH mapping to monitor pH e in HCC, which could be a biomarker for metabolic changes and monitoring tumor aggressiveness and therapeutic outcome. [55][56][57] Tumor acidosis is the consequence of lactate and H + ions accumulation, which are produced by glycolysis and oxidative metabolism. Most tumor cells, also called as glycolytic tumor cells, prefer glycolysis rather than OXPHOS, leading to increases in lactate and H + production.…”
Section: Acid-base Microenvironmentmentioning
confidence: 99%